The impact of the experimental “Hypoxic Boxing” training on the motor abilities and specialized fitness of national boxing champions: a randomized controlled trial - Ambroży, Tadeusz; Snopkowski, Piotr; Rydzik, Łukasz; Kędra, Andrzej; Wąsacz, Wojciech (Frontiers in Physiology, 2025)
IntroductionAmong theorists and practitioners, there is a consensus regarding the significant role of optimizing sports training in high-altitude conditions. This stems from the specific combination of environmental variables that determine the dynamics of changes in broadly understood training adaptation. The aim of this study was to evaluate the impact of an experimental training program, Hypoxic Boxing (under normobaric hypoxia conditions), on the development of the functional profile (motor and specialized fitness) within a national elite group of boxers.MethodsA randomized controlled trial was conducted with 20 elite-level boxers representing the national championship level (mean age: 23.9 ± 3.0 years; height: 181.3 ± 7.14 cm; body weight: 79.3 ± 8.84 kg; BMI: 24.15 ± 2.21; training experience: 10 ± 4.0 years). The participants were assigned to either the experimental group (Hypoxic Boxing - HB; n = 10) or the control group (Normoxic Boxing - NB; n = 10). Both groups followed the same 6-week training program, which included two daily training sessions (morning and afternoon). The afternoon training sessions for the HB group were conducted under normobaric hypoxic conditions in a hypoxic chamber, while the NB group trained in non-simulated normoxic conditions. The profile of changes was assessed before and after the intervention (pretest vs. posttest) by analyzing the results of selected motor ability tests from the Eurofit battery and specialized fitness using the Pawluk Boxing Test.ResultsThe HB group (within-group analysis) demonstrated a significant improvement in test performance for strength endurance and resistance to fatigue in the abdominal, arm, and back muscles. Specifically, the number of sit-ups increased from 27.5 ± 4.0 to 28.8 ± 3.4 (p = 0.007, dc = 0.35), and the number of pull-ups improved from 14.9 ± 4.5 to 16.4 ± 4.6 (p = 0.005, dc = 0.33). The intervention also led to a notable enhancement in specialized fitness, including anaerobic capacity and technical efficiency, as reflected in the number of punches delivered in 20 s (72.6 ± 9.6 to 74.3 ± 9.5, p = 0.008, dc = 0.18), post-exercise recovery (HR 1 min: 143.3 ± 6.6 to 138.4 ± 5.8 bpm, p = 0.004, dc = 0.79), and the multidimensional Index of Specialized Performance (4.5 ± 0.5 to 4.3 ± 0.5, p = 0.005, dc= 0.40). These changes were not observed in the NB group (p > 0.05). Additionally, the HB group showed increased homogeneity in performance outcomes during the post-test phase. The intergroup comparison of training effects after the experiment revealed significant differences in the overall dimension of special fitness (p > 0.05), with a more favorable improvement observed in the HB group.ConclusionHypoxic Boxing demonstrates the benefits of an extended, combinatory training program compared to standard protocols. Our findings hold both scientific and practical significance, as Hypoxic Boxing appears effective in enhancing selected motor abilities and multidimensional specialized fitness. Further research is needed to better understand the potential benefits and limitations of hypoxic training for combat sports athletes.